2018
DOI: 10.1101/453985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein-protein binding pathways and calculations of rate constants using fully continuous explicit solvent simulations

Abstract: A grand challenge in the field of biophysics has been the complete characterization of proteinprotein binding processes at atomic resolution. This characterization requires the direct simulation of binding pathways starting from the initial unbound state and proceeding through states that are too transient to be captured by experiment. Here we applied the weighted ensemble path sampling strategy to enable atomistic simulation of protein-protein binding pathways. Our simulation generated 203 fully continuous bi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 49 publications
3
32
0
Order By: Relevance
“…These findings are not contradictory, as hydrophobic interactions are generally found to be the driving interactions in protein-protein complexes, whereas the long-range electrostatic interactions are steering in the complex formation and contribute to interaction specificity. 90,[99][100][101] In agreement with the results of Fatima et al 20 , we have found that addition of NaCl promotes complex formation (Supplementary Figure S19), which indicates that hydrophobic interactions stabilize the albumin-detemir complex.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are not contradictory, as hydrophobic interactions are generally found to be the driving interactions in protein-protein complexes, whereas the long-range electrostatic interactions are steering in the complex formation and contribute to interaction specificity. 90,[99][100][101] In agreement with the results of Fatima et al 20 , we have found that addition of NaCl promotes complex formation (Supplementary Figure S19), which indicates that hydrophobic interactions stabilize the albumin-detemir complex.…”
Section: Discussionsupporting
confidence: 90%
“…Given that these transitions are much faster than the waiting times, 16,17 the WE strategy can be orders of magnitude more efficient than conventional MD simulations in generating pathways for rare events such as protein folding and protein binding. 18,19 This efficiency is even higher for slower processes, increasing exponentially with the effective free energy barrier. 20 Not only are dynamics carried out without any biasing force or modifications to the free energy landscape, but suitable assignment of statistical weights to trajectories provides an unbiased characterization of the system’s time-dependent ensemble properties.…”
Section: Introductionmentioning
confidence: 99%
“…This study shows that hypersound-stimulated MD simulations have the potential to accelerate proteinligand binding kinetics through a solvent-mediated mechanism without collapse of the protein structure, thus enabling atomic-scale observation of ligand-binding processes within time scales accessible by standard MD (~ 100 ns). In contrast to other advanced MD methods that accelerate biomolecular processes 25,26 , this method does not require prior knowledge of the protein-ligand complex structure. In this way, the simulations can provide signi cant insights into fundamental biological mechanisms (such as the discovery of microscopic ligand binding pathways involving various bound conformations) and facilitate drug discovery (as illustrated by the present exploration of druggable binding sites on the protein surface).…”
Section: Main Textmentioning
confidence: 99%